المسؤولية التضامنية في الشركة - ساعو, فريال; بايو, رانية (جامعة مولود معمري, 2022)
تعتبر المسؤولية التضامنية من الضمانات القانونية التي كرسها المشرع الجزائري لحماية الغير المتعامل مع الشركة، حيث تقوم على فكرة تقاسم الأعباء والديون بين الشركاء واتحاد ذمتهم المالية في سبيل تحقيق ذلك. تعتمد المسؤولية التضامنية على وجود الاعتبار الشخصي في الشركة، إذ أن الشركات القائمة على الاعتبار المالي يصعب تطبيق هذا النوع من المسؤولية عليها، بالنظر إلى اقتصار تحمل المسؤولية لدى الشريك بقدر الحصة المقدمة، على خلاف الشريك في شركات الأشخاص الذي يتحمل مسؤولية مطلقة، غير أن هذا القول لا يمنع تطبيق هذه المسؤولية على شركات الأموال بشكل نسبي في حالات محددة تتعلق بتواجدها ضمن وضعيات قانونية تستوجب إعمال المسؤولية التضامنية كما هو الشأن بالنسبة لبطلان الشركة وتصفيتها، أو بسبب حالات ترتبط بالمركز القانوني للشريك، الذي قد يتعرض عند مباشرته للنشاط في إطار الشركة إما للوفاة أو الانسحاب أو الإفلاس الأمر الذي يستدعي.
Keywords: Contrepartie personnelle; RSE; Responsabilité conjointe; Responsabilité sociale; Société en coentreprise; Société par actions; Société à responsabilité conjointe; Sociétés de capitaux; Sociétés personnelles; الاعتبار الشخصي; الشركة; المسؤولية الاجتماعية; المسؤولية التضامنية; شركات الأشخاص; شركات الأموال; شركة التضامن; شركة المحاصة; شركة المساهمة

La lutte contre la contrefaçon des vins français dans le commerce international - Dubois, Marie-Clémence (Université de Lille, 2022)
Keywords: Commerce international; Vin – Faux – Lutte contre

Les contrats de partenariats Public-Privé, un succès rapide dissimulant beaucoup de risques : le cas de l'aéroport international Blaise Diagne de Dakar - Badji, Henry Michel Kader (Université de Liège, 2022)
Le continent Africain, un territoire avec un grand potentiel ! Près de la moitié des 20 pays à la croissance la plus rapide au monde au cours des cinq dernières années sont localisés en Afrique. Les investisseurs sont attirés par, le coût faible de la main d’œuvre, la stabilité socio-politique mais aussi et surtout par le potentiel que représente l'urbanisation et l'importance croissante de la classe moyenne. Cependant, cette croissance économique pourrait être freinée par le manque d'infrastructures du continent (routes, voies ferroviaire, ports, hôpitaux de dernière génération etc.…). Les besoins en infrastructures en Afrique subsaharienne sont estimés à plus de 93 milliards de dollars par an au cours de la prochaine décennie, et seule la moitié est disponible aujourd’hui. Les partenariats public-privé (PPP) sont donc apparus comme une alternative pour ce déficit de financement constaté. Au Sénégal, le peu de projets financés jusqu’ici avec le modèle PPP ont suscité d’énorme débats publics. La population se pose beaucoup de questions sur les avantages et inconvénients de ce type de marché. Mais à ces différentes questions, le gouvernement apporte rarement de réponses persuasives. Notre étude de recherche se veut donc, d’identifier à travers la littérature sur les PPP, mais aussi en nous appuyant sur l’analyse d’un grand projet de construction d’un aéroport, exécuté au Sénégal sous le modèle PPP, l’ensemble des risques rattachés à ce type de contrat. Le but étant de proposer à la fin de l’étude, un outil de gestion et d’anticipation sur ces risques.
Keywords: Afrique; Gestion des risques; PPP; Partenariats Public-Privé; Sénégal

L’internationalisation de la marque : entre possibilités et stratégies - Taillez, Morgane (Université de Lille, 2022)
Keywords: Mondialisation; Stratégie de marque

Fraude ao Mercado de Capitais e a responsabilidade civil objetiva da companhia perante os seus Investidores - Abreu, Alex de Souza (Pontifícia Universidade Católica de São Paulo, 2022)
The Brazilian legal system, especially Law n. 6,385, December 7, 1976 (Capital Market Law), the Corporate Law (LSA) and regulations of the Securities and Exchange Commission (CVM), although they have a complex system of accountability for illegal acts, do not provide for accountability company in relation to investors. The objective of this study is to verify the limits of damages in relation to the company versus a shareholder or a third part; analyze the spectrum of direct and indirect damages; and understand if there are and what elements are necessary to verify these damages and can also be directly affected. The methodology to be used in this study is deductive, through a bibliographic and documentary approach, by reading works, scientific articles, dissertations and theses on the subject, as well as the revision of the legislation that applies to the subject. The study brings as results and conclusions that without excluding the system of responsibility of the administrators and other bodies of the company, it is the duty of this to indemnify the damages caused to the investors of the capital market, since the former are mere instruments of manifestation of their will
Accepted: 2022-11-03T18:39:31Z
Keywords: Accountability of publicly held companies; Capital market; Damage to investors; Danos aos investidores; Mercado de capitais; Responsabilização de companhias abertas

La réforme du droit OHADA des investissements : une éradication des pratiques contractuelles déloyales par l’introduction d’un Acte uniforme relatif aux investissements - Dzama, Pollyana Marguerita Milaine Awé (Université de Montréal, 2022)
Cette ébauche est une contribution au développement économique des Etats d’Afrique subsaharienne, en particulier ceux membres de l’OHADA. Elle répond à une problématique qui nuit au développement économique de ces États par la voie de l’investissement : celle de la mise en place d’un système juridique africain permettant d’asseoir des règles juridiques pertinentes, fondamentales à l’encadrement du champ des investissements en Afrique. Quoiqu’il existe déjà au niveau national et communautaire africain, des législations applicables en la matière, cette étude démontre l’insuffisance de ces règles, trop promotrices des investissements, et peu protectrices de leurs enjeux, à régir comme il se doit le domaine des investissements. Cette étude est de ce fait révélatrice d’une nécessité, d’une opportunité : celle de la réforme du système juridique africain des investissements par l’instauration d’un Acte uniforme OHADA relatif aux investissements (AUI). Le dispositif normatif de cet Acte uniforme se voudra à la fois préventif et curatif des irrégularités pouvant être commises par les acteurs publics africains et leurs partenaires occidentaux dans les phases de négociation des conventions d’investissement, d’admission de l’investissement, d’exécution et d’extinction de l’activité d’investissement mais aussi protecteur des enjeux sociaux et environnementaux liés à l’exécution des projets d’investissement en Afrique. Cette réforme est également le lieu de veiller aux intérêts économiques des États africains lors des partenariats économiques conclus avec les États occidentaux et entreprises occidentales, au respect par leurs partenaires du droit interne et communautaire africain objet de la réforme mais également de protéger les investisseurs étrangers face aux actes préjudiciables émanant des acteurs publics africains. L’effectivité de telles mesures n’est possible que par l’institution d’un organe communautaire africain (la CARICI : Cour Africaine de Répression des Infractions Commises en matière d’Investissement) qui aura pour mission le suivi de l’exécution des projets d’investissements conformément aux programmes ou plans d’investissements agréés et aux dispositions juridiques qui seront établies par ledit Acte uniforme relatif aux investissements. Telles sont les suggestions émises lors de la rédaction de ce travail de recherche, qui nous l’espérons concourras à une grande avancée du droit des investissements africains et par voie de conséquence à une croissance économique fulgurante de ce continent. This study is a contribution to the economic development of sub-Saharan African states, in particular those that are members of OHADA. It responds to a problem that is detrimental to the economic development of these States through investment: that of the establishment of an African legal system making it possible to establish relevant legal rules, fundamental to the supervision of the field of investment in Africa. Although legislation already exists at the national and community level in Africa, this study shows the inadequacy of these rules, which are too promotive of investments and offer little protection to those at stake, to govern the field of investments as they should. This study is therefore indicative of a need and an opportunity: that of reforming the African legal system for investments through the introduction of an OHADA Uniform Act on Investments (UAI). The normative mechanism of this Uniform Act is intended to be both preventive and curative of irregularities that may be committed by African public actors and their Western partners in the phases of negotiation of investment agreements, admission of the investment, execution and termination of the investment activity; but also protective of the social and environmental issues related to the execution of investment projects in Africa. This reform is also the place to watch over the economic interests of African States during economic partnerships concluded with Western States and Western companies, the respect by their partners of African domestic and community law which is the subject of the reform, but also to protect foreign investors against prejudicial acts emanating from African public actors. The effectiveness of such measures is only possible through the institution of an African community body (the ACRIO: African Court of Repression of Investment Offences) which will have as its mission the monitoring of the execution of investment projects in accordance with the approved investment programmes or plans and the legal provisions which will be established by the said Uniform Act on Investments. These are the suggestions made during the drafting of this research work, which we hope will contribute to a great advance in African investment law and consequently to a dazzling economic growth of this continent.
Keywords: Acte uniforme relatif aux investissements; Droit OHADA des investissements; Investissements; Investments; Law enforcement; OHADA investment law; Pratiques contractuelles déloyales; Unfair contractual practices; Uniform Act on Investment

Free movement of goods and new agreements in the aftermath of Brexit - Police, Cecilia (LUISS Guido Carli, 2022)
The main principles of EU internal market vs the new UK internal market: a background. The internal market of the European Union. UK membership: accession to the European economic community in 1973. The nature of the EU internal market and the free movement of goods. The UK internal market after the internal market act 2020. The EU common commercial policy and the post-Brexit scenario. Brexit: new agreements and legal framework. EU-UK post-Brexit relationship: a new framework for a new partnership. Brexit history and the question of sovereignty. Brexit history: the timeline. Brexit and the withdrawal agreement. Brexit and Northern Ireland protocol. Brexit and trade: perspectives on a new partnership. Brexit and trade: trade and cooperation agreement. Trade and cooperation agreement: EU-UK trade relations, institutional and governance structures. Preliminary remarks. Analysis of the TCA: trade in goods provisions. 0,0 agreement: zero tariffs, zero quotas and rules of origin. The TCA: technical barriers to trade (TBT). The TCA: sanitary and phytosanitary standards (SPS). The TCA: the principle of mutual recognition. Level playing field (LPF). The Northern Ireland protocol and the trade in goods regime. TCA’s main concerns and application issues. TCA dispute settlement mechanisms. Some conclusive remarks on TCA provisions.

آليات تقييم الصيرفة الاسلامية في البنوك التجارية وتحدياتها -دراسة حالة البنك الوطني الجزائري - ساعد, بن; الحميد, عبد (Ibn Khaldun University of Tiaret, 2022)
يعتبر النظام المصرفي من بين الأسس التي يعتمد عليها النشاط الاقتصادي لأي مجتمع و ذلك بالنظر لأهمية الدور الذي يلعبه في المساهمة في إمداد النشاط الاقتصادي بالأموال، اللازمة من اجل تنميته و تطوي ره ، وقد اجمع الباحثون الاقتصاديون على أن من بين أسباب الأزمات المالية ترجع إلى الأسلوب الربوي المتبع من طرف البنوك التقليدية، خصوصا بعد أن ضربت الأزمة المالية العالمية عصب الاقتصاد الرأسمالي سنة 2008 وهزت اقتصاديات الدول وأضعفت البنوك التجارية خلافا عن البنوك الإسلامية والبنوك التجارية ذات الشبابيك الإسلامية ، ومن هذا المنطلق ازدادت الحاجة إلى وجود بنوك تعمل وفقا للشريعة الإسلامية والتي تقوم على أساس إلغاء الفائدة وعدم التعامل بالربا في تعاملاتها، ومنه فقد أصبحت هذه البنوك لاعبا مؤثرا وبارزا في اقتصاديات الدول الإسلامية و العالمية و التي من بينها الجزائر التي اتجهت هي الأخرى للدخول إلى عالم الصیرفة الإسلامية باعتمادها لافتتاح نوافذ إسلامية على مستوى البنوك العمومية. ومن خلال دراستنا توصلنا الى أن البنوك العمومية الجزائرية تحاول خوض تجربة فتح شبابيك إسلامية وقد خلصنا بأن اعتماد هذه البنوك على آلية التعامل بشبابيك تعمل وفق قواعد الشريعة الإسلامية في معاملاتها المالية من شأنه أن يحقق استقطاب ورضا الزبائن. The banking system is considered one of the foundations on which the economic activity of any society is based, given the importance of the role, it plays in helping to supply economic activity with the funds necessary for its operation. Economic researchers have agreed that among the causes of financial crises are due to the usurious method adopted by banks, especially after the global financial crisis hit the backbone of the capitalist economy in 2008, shook the economies of the countries, and weakened commercial banks unlike Islamic banks and commercial banks with Islamic windows From this point of view, the need has grown for the existence of bank operating in accordance with Islamic law, which is based on the abolition of interests in their financial transactions, these banks have become an influential and leading actor in the economies of Islamic countries including Algeria, which has also tended to enter the Islamic banking world by adopting it to open Islamic windows at the level of public banks. Through our study, we concluded that Algerian public banks are trying to live with the opening of Islamic counters, and we concluded that the dependence of these banks on the processing mechanism of counters that operate according to the rules of Islamic Sharia law in their financial transactions, would attract and satisfy customers.
Keywords: Banques commerciales; Banques islamiques; Fenêtres islamiques; Satisfaction client; البنوك الإسلامية; البنوك التجارية; النوافذ الإسلامية; رضا الزبائن

دراسة تحليلية للبيئة اللوجيستية و البيئة القانونية للتجارة الالكترونية في الجزائر - بوسيف, عبد القادر أسامة; زاوي, أسماء (Ibn Khaldun University of Tiaret, 2022)
هدفت الدراسة الى تحليل كل من البيئة القانونية و البيئة اللوجستية و مدى تأثيرها على التجارة الالكترونية في الجزائر، وتوصلت الى أن البيئة القانونية هي جد مناسبة و تواكب العصرنة و ان التعديل الأخير في قانون التجارة الالكترونية أثمر عن مواد جد مناسبةومحفزة للتجارة الالكترونية في الجزائر، بالرغم من ذلك، لم تجد التجارة الإلكترونية بعد مكانتها في الجزائر ولم تحقق بعد الآن الانطلاقة المرجوة، يعود السبب في ذلك لكون البيئة اللوجستية لا تزال متأخرة و لا تواكب التطور الهائل الحاصل في هذا المجال، وأنه على الجزائر العمل على تطوير بيئتها اللوجستية بمسايرة التقدم التكنولوجي في العالم من أجل إعطاء دفعة للنهوض بهذا النوع من التجارة و إعتمادها كأسلوب حديث للتبادل التجاري في الجزائر. The study aimed to analyze both the legal environment and the logistics environment and their impact on e-commerce in Algeria. The study concluded that the legal environment is very suitable and keeps pace with modernity, and that the recent modification of the law on electronic commerce has resulted in very appropriate and stimulating articles for electronic commerce in Algeria. However, e-commerce has not yet found its place in Algeria and has not yet achieved the desired breakthrough, the reason is that the logistics environment is still lagging behind and not keeping pace with the enormous development of international e-commerce, and that Algeria should work to develop its logistics environment to keep pace with technological advances in the world in order to give impetus to the advancement of this type of commerce and its adoption as modern mode of commercial exchange in Algeria.
Keywords: Commerce électronique; Environnement juridique; Environnement logistique; Paiement électronique; البيئة القانونية; البيئة اللوجيستية; التجارة الإلكترونية; الدفع الإلكتروني

النظام القانون للمؤسسات الناشئة في الجزائر - وناس, علي (Ibn Khaldun University of Tiaret, 2022)
الغاية من هذه الدراسة هو تسليط الضوء على المقاولاتية في مجال المال و الأعمال في عصرنة للنشاط التجاري بكل ركائزه منها ريادة الأعمال فظهرت المؤسسات الناشئة كخيار إستراتيجية انتهجته الجزائر و الذي فرضته العولمة و اقتصاد المعرفة المبني على تكنولوجيا المعلومات و الاتصال من أجل النهوض بالاقتصاد الوطني لتحقيق التنمية المستدامة بعيدا عن الريع. إن اهتمام الدولة بالمؤسسات الناشئة ككيان قانوني يختلف كليا عن الشركات التجارية التقليدية لأنها ترتكز على الإبداع و التكنولوجيا و سرعة النمو بأقل تكلفة، لذا خصها المشرع الجزائري بترسنة من النصوص القانونية لتحديد طبيعتها القانونية و توفير مناخ أعمال مناسب لنشاطاتها تجسدت في المرسوم التنفيذي رقم 20 - 254 المتعلق بإنشاء المؤسسات الناشئة و الحصول على علامة "مؤسسة ناشئة" و "مشروع مبتكر" و "حاضنة أعمال" و في القانون رقم 22 - 09 الذي حدد الشكل القانوني للمؤسسات الناشئة تحت عنوان "شركة المساهمة البسيطة". كما دعمها بآليات مختلفة تمثلت في صندوق خاص بتمويلها و حاضنات أعمال تسهر على تدريب فريق عملها و مرافقتها و متابعتها طيلة مراحل حياتها،إضافة إلى مزايا إعفاء جبائية. توصلت الدراسة إلى الاهتمام الكبير و الخاص بالمؤسسات الناشئة كونها الحل الاستراتيجي لتحريك عجلة التنمية الاقتصادية و تحقيق القيمة المضافة في الجزائر وضمان نجاحها. The purpose of this study is to shed light on entrepreneurship in the field of money and business in the modernization of commercial activity with all its pillars, including entrepreneurship. The emerging enterprises appeared as a strategic option adopted by Algeria, which was imposed by globalization and the knowledge economy based on information and communication technology in order to advance the national economy to achieve development sustainable without rent. The state’s interest in emerging enterprises as a legal entity is completely different from traditional commercial companies because they are based on creativity, technology and rapid growth at the lowest cost, so the Algerian legislator singled out them with an arsenal of legal texts to determine their legal nature and provide a suitable business environment for their activities embodied in Executive Decree No. 20-254 Related to the establishment of start-ups and obtaining the marks of “startup institution”, “innovative project” and “business incubator” and in Law No. 22-09 that defines the legal form of start-ups under the title “Simple Joint Stock Company”. He also supported her with various mechanisms represented in a special fund to finance her and business incubators that ensure the training of her work team, accompany her and follow up on her throughout her life, in addition to the advantages of a tax exemption. The study found a great interest in emerging institutions as a strategic solution to move the wheel of economic development and achieve added value in Algeria and ensure its success.
Keywords: Développement durable; Société par actions à responsabilité limitée; Startups; Économie de la connaissance; اقتصاد المعرفة; التنمية المستدامة; المؤسسات الناشئة; شركة المساهمة البسيطة

La responsabilité du transporteur suborbital de personnes : un régime à construire - Venancie, Sarah (Université de Montréal, 2022)
Les transports suborbitaux privés peuvent être définis comme tout vol réalisé au moyen d’un véhicule aérospatial, capable d’atteindre une très haute altitude et d’évoluer dans les couches supérieures de l’atmosphère terrestre, sans pour autant être mis en orbite. Plusieurs entreprises ont pour projet de faire des vols suborbitaux, le mode de transport de personnes à grande vitesse de demain. Dans l’hypothèse d’un tel développement, la réflexion autour de la règlementation de ces activités devient primordiale. Les activités suborbitales ont la particularité de prendre place à la fois dans l’espace aérien et dans l’espace extra-atmosphérique et pour ce faire, empruntent autant les caractéristiques techniques de l’aéronef que de l’engin spatial. Il est donc particulièrement difficile de les qualifier du fait qu’il existe plusieurs corpus législatifs susceptibles de régir ces vols : le droit aérien, le droit spatial ou un nouveau régime qu’il conviendrait alors d’imaginer. Sans prétendre à l’exhaustivité, ce mémoire envisagera les différentes options normatives pouvant permettre de règlementer la responsabilité du transporteur suborbital de personnes lorsqu’il cause un dommage au participant durant le vol. Le cas échéant, nous proposerons les meilleures alternatives pouvant permettre d’assurer le développement pérenne de ce secteur d’activité, tout en garantissant un haut niveau de sécurité juridique pour l’ensemble des parties prenantes, participants comme opérateurs spatiaux. Private suborbital transportation can be defined as any spaceflight by an aerospace vehicle capable of reaching a very high altitude into the edge of space without reaching orbital velocity. For now, the aim of those activities is to offer customers direct experience with space travel. However, the ultimate goal is to provide high speed flights between various point of the Earth. When this objective will be achieved, the need to promulgate an integrated and uniform legal regime will be of great importance in order to facilitate and secured commercial aerospace activities expansion. Private suborbital activities have the dual specificities of using a vehicle that use either astronautic et aeronautics technology in order to achieve lift and thereby flying in air space, and also traveling through outer space during a small portion of the flight. This hybrid nature raises legal uncertainties about the applicable legal regime that could be one of air law, space law or a new regime that would need to be invented. This essay will focus on the specific issues surrounding liability. In other terms, it will focus on the different options that are available to manage liability issues that will arise between spaceflight participant and spaceflight operators and the way it will impact disputes when an accident occurs. Then, we will make a proposal for solutions that would best preserve the economic needs of this emerging industry, while insuring legal certainties for both spaceflight operators and participants.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/27018/Venancie_Sarah_2021_Memoire.pdf
Keywords: Aerospace transportation; Aircraft; Aéronef; Dommages corporels; Espace; Liability; Objet spatial; Physical injury; Responsabilité; Space; Space object; Space tourism; Suborbital transportation; Tourisme spatial; Transport aérospatial; Transport suborbital

A tutela da proteção de dados pessoais na era digital: uma análise da cooperação internacional entre o BRICS - Silva, Rafaela Nicolazzi Corrêa da (Universidade de São Paulo, 2022)
Este trabalho busca analisar os atuais modelos e mecanismos para a cooperação internacional sobre a tutela da proteção de dados pessoais com o propósito de verificar quais os instrumentos que os países Brasil, Rússia, Índia, China e África do Sul devem considerar para estreitar seus laços de colaboração no grupo BRICS em prol de suas economias e negócios sem olvidar a proteção ao direito à privacidade e proteção de dados pessoais. Partese da hipótese de que, apesar de suas diferenças como nações heterogêneas e diversas, o BRICS possui o ânimo de cooperar em matéria de tecnologia, informação e comunicações e o tema de proteção de dados pessoais torna-se área essencial para a data driven economy e reconhecida por estes Estados. A tutela da proteção de dados pessoais está presente na construção legislativa de jurisdições distintas e que também exercem influência nos países do BRICS, como os modelos europeu e norte-americano. Conclui-se apontando que os modelos existentes de cooperação internacional sobre proteção de dados pessoais devem ser considerados pelo BRICS para o balanceamento de colaboração e desenvolvimento de garantias que assegurem a proteção de dados pessoais e a promoção de oportunidades de negócios para suas economias e desenvolvimento de seus interesses comerciais.
Keywords: BRICS; China; Cooperação internacional; Direito comparado; Estados Unidos; Europa; Integração econômica internacional; International cooperation; Privacidade; Protection of personal data; Proteção de dados pessoais; Right to privacy and data protection; Rússia; África do Sul; Índia

L'attractivité de l'arbitrage au regard des nouvelles réformes de l'OHADA - Kounouho, Marcson Smile Geoffroy Tagnon (Université d'Abomey-Calavi, 2022)

A tributação das sociedades não residentes sem estabelecimento estável no sistema fiscal guineense - Nhaga, Justino (Universidade de Lisboa, 2022)
Nesta dissertação estudamos, como ponto principal, a estrutura do sistema fiscal guineense e da tributação aplicável às sociedades não residentes sem estabelecimento estável na Guiné-Bissau. Tivemos de estudar alguns aspetos da tributação das sociedades residentes e não residentes com estabelecimentos estáveis: os critérios de determinação da residência fiscal tanto no Direito Fiscal Internacional (DFI), assim como no Direito Fiscal Guineense (DFG); os elementos de conexão, aferição do estabelecimento estável (EE), tipos e conceitos de EE e do lucro imputável ao EE. Achamos pertinente e com isso procuramos abordar sinteticamente os fundamentos que legitimam o Estado guineense a tributar os rendimentos obtidos no território por sociedades não residentes sem estabelecimento estável. É sabido que não existe uma única definição para Estabelecimentos Estáveis, mas sim diferentes conceitos que variam de sistema para sistema e que podemos agrupar estes em dois polos, conforme estejamos a falar dos sistemas de países desenvolvidos ou de países em vias de desenvolvimento. Mas, pelo objetivo traçado, somos obrigados a analisar o conceito de estabelecimento estável adotado pelo legislador guineense1. Pese embora para efeitos de atualização e análise critica, não podemos abdicar de chamar à colação as novas formas de desenvolver atividades económicas trazidas pelas novas tecnologias e pela globalização que colocam em causa os tradicionais conceitos de estabelecimento estável adotados pelos Estados. Seguidamente, entramos na parte nuclear da nossa dissertação, expondo o regime jurídico aplicável aos sujeitos em causa e a aplicação de diferentes soluções. Concomitantemente, consoante sejam sociedades não residentes sem estabelecimento estável (o centro de atenção) ou não residentes com estabelecimento estável (assunto subsidiário), com destaque para o primeiro grupo. Neste círculo, levantamos questões bastante específicas, muitas delas de difícil compreensão e até de índole politica, que nos levaram a apreciações, as quais foram obviamente limitadas por este ser um trabalho pura e simplesmente académico e não socioeconómico e politico. Finalmente, este exercício académico nunca ficaria minimamente completo sem que se discutisse a questão da necessidade de receita fiscal, concorrência fiscal e os esforços que o Estado tem vindo a enveredar no sentido de incentivar e atrair mais investimentos. Com uma política mais atrativa, torna-se mais eficaz e eficiente a diversificação da economia, sendo que isto só é possível com a presença de grandes empresas a operar nos diferentes setores da economia no território. Deverá pois, não ser só acompanhada da eliminação da pesada burocracia, da excessiva intervenção do poder politico no sistema e da dupla tributação (económica ou jurídica2), visto que são verdadeiros constrangimentos para os operadores económicos. Mas também a criação de critérios consistentes e claros da concessão de benefícios fiscais3 e da eliminação da dupla não tributação também prejudiciais para o erário público dos Estados. Os resultados destas análises revelaram os problemas dos aspetos socioeconómicos e financeiros inerentes ao índice do desenvolvimento humano (IDH). A Guiné-Bissau dispõe de recursos naturais, sendo que a grande maioria continua por explorar. Porém, mesmo tendo os recursos naturais disponíveis, a dependência de ajudas externas para resolver as suas necessidades pontuais é persistente e contínua.
Keywords: Direito fiscal; Globalização; Guiné-Bissau; Poder tributário; Sociedades sem estabelecimento estável; Tributação

La règlementation de la décarbonation du transport maritime - Alavoine, Zoé (Aix-Marseille Université, 2022)
Keywords: Droit maritime; Décarbonisation; Transport maritime

La clause merchant - Arista, Pauline (Aix-Marseille Université, 2022)

La libéralisation des règles de propriété et de contrôle des transporteurs aériens communautaires dans le système bilatéral international - Barron, Lisa (Aix-Marseille Université, 2022)

L'avarie commune - Besse, Ilana (Aix-Marseille Université, 2022)

Définir et mettre en oeuvre une offre de services de communication performante à destination des compagnies aériennes afin de faciliter et de rationaliser le processus de gestion des taxes aéronautiques dans la perspective de la certification qualité du Secrétariat Général de la DGAC - Booms, Mélodie (Aix-Marseille Université, 2022)

L'impact de la guerre russo-ukrainienne sur le transport aérien mondial - Chevalier, Hermance (Aix-Marseille Université, 2022)

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

Les enjeux de la sûreté ferroviaire à la SNCF - Escaut, Sébastien (Aix-Marseille Université, 2022)

Le conflit russo-ukrainien : conséquences dans l'industrie maritime et des transports - Faverot Quilichini, Clara (Aix-Marseille Université, 2022)

La culture de sécurité aérienne : un défi à l’échelle internationale - Frikh, Amira (Aix-Marseille Université, 2022)

Modalités et enjeux d'une ouverture de ligne aérienne de transport de passagers - Gerard, Charles-Emile (Aix-Marseille Université, 2022)

The role of good faith in South African contract law - Govender, Tashri (University of KwaZulu-Natal, 2022)
This research paper seeks to address the role that good faith plays in South African contract law by first discussing its origin and then chronologically tracing its position from pre-1994 to today. The judgements of both the Supreme Court of Appeal and the Constitutional Court will be unpacked, as a means to understand the development of good faith over the years. The position that good faith plays in foreign jurisdictions will also be discussed, for the sake of achieving a universal understanding of how good faith is perceived around the world. The research concludes by placing good faith in its current role and context in South Africa, and also proposing a way forward.
Keywords: Bona fides; Contract Law

La responsabilité du manutentionnaire - Hubert, Solène (Aix-Marseille Université, 2022)

L'Essor du transport de marchandises par voie aérienne face aux enjeux environnementaux croissants - Jamal, Oumayma (Aix-Marseille Université, 2022)

A critical analysis of the institution of business rescue proceedings during liquidation proceedings - Krishundutt, Sanam (University of KwaZulu-Natal, 2022)
South Africa is currently undergoing harsh economic times, and as such, many companies are feeling the brunt of the situation. As a result, these companies begin to trade at a loss and are left without any other option but to liquidate their affairs in order to pay off creditors. However, with the development brought by the Companies Act 71 of 2008 (“the Act”), business rescue was introduced. Business rescue is an alternative to liquidation and it allows the company to undergo rehabilitation and continue trading if certain requirements are met. Chapter 6 of the Act aims to assist businesses in providing some sort of relief in the form of business rescue to provide them with the breathing space that they require to try and become a viable business again. Just like any new formulated concept, it is susceptible to abuse. Many companies that are already under liquidation are suspending their liquidation in favour of business rescue, despite, in some instances, the liquidation order having already been granted against the company. The Covid-19 pandemic has made the question of whether a business can suspend liquidation proceedings in favour of business rescue more prevalent as the pandemic has caused a detrimental financial impact on a number of businesses. Now more than ever businesses find themselves struggling to keep afloat, and as a result many of them have to consider the avenues of liquidation or business rescue. This dissertation aims to look at both liquidation and business rescue proceedings and decipher whether the courts were correct in their decision regarding when business rescue proceedings can be instituted during liquidation proceedings. The importance of taking into account the above is due to the fact that many companies in present day are experiencing financial difficulties, and liquidation or business rescue proceedings are the options that they are left with. However, one has to carefully consider both options, taking into account the company’s financial circumstances. This is of importance, as one needs to establish if there is a reasonable prospect of rescuing the company or not. If there were, then business rescue would indeed be the route to be taken, but if not, then liquidation proceedings would be. However, many companies that have no prospect of being rescued, and that have already opted for liquidation may want to institute business rescue proceedings to delay the inevitable and frustrate creditors, thus leading to the abuse of the newly formulated concept, which has to be curbed.
Keywords: Business failure; Companies Act 71 of 2008; South Africa

Le déploiement d’un programme de Compliance Anti-corruption au sein d’une multinationale - Leroy, Romane (Aix-Marseille Université, 2022)

A critical analysis of the role, appointment, and powers of a business rescue practitioner - Luthuli, Bayanda Nompumelelo (University of KwaZulu-Natal, 2022)
No abstract provided.
URI: https://researchspace.ukzn.ac.za/handle/10413/20930
Keywords: Corporate rescue regime; Financially distressed companies; Judicial management

L’impérative adaptation des politiques européennes et internationales en réponse à la concurrence du transport aérien - Martinez, Barbara (Aix-Marseille Université, 2022)

The abuse of dominant position in digital markets: Google Shopping case - Moroni, Filippo (LUISS Guido Carli, 2022)
Abuse of dominance in the digital markets. Digital markets. Art.102 TFEU: how can it be applied to digital markets? A global perspective: the evolution of the abuse of dominance in digital markets around the world. Europe: the proposal for a regulation on contestable and fair markets in the digital sector (digital market act). United States of America: a time for reforms. China: a new approach towards digital markets. The Google Shopping case: the first step for competition enforcement in digital markets. The European Commission decision (AT.39740). The general Court decision (T-612/17). The Google case in the US: completely different results. A glimpse into the future: the Google Shopping case under the DMA.
Keywords: Abus de position dominante; Competencia; Competition law; Concurrence; Dominant position; Monopole

Les aéroports métropolitains français face à la concurrence : l'enjeu de la compétitivité - Mossard, Maxime (Aix-Marseille Université, 2022)

Uluslararası muhasebe standartları ile OHADA muhasebe sisteminin karşılaştırılması - Moussa Hisseine, Amine (Sakarya Üniversitesi, 2022)
Ekonomilerin küreselleşmesi ve piyasaların globalleşmesi karşısında, ortak bir dile sahip olma arzusu giderek daha fazla hissedilmektedir. Bu ihtiyacı hafifletmek için dünya çapında, birçok ülke, kalite ve karşılaştırılabilir bilgiler için UFRS standartlarını benimsemenin uygun olduğunu düşünmüştür. Bu momentumda, SYSCOHADA muhasebe sistemi aracılığıyla OHADA alanı, 2017 yılında standartlarını UFRS ile uyumlu hale getirmeye karar vermiştir. Bu çalışmanın amacı, Uluslararası Muhasebe Standartlarını (UMS/UFRS), on yedi ülkedeki tüm varlıklarının muhasebesini yöneten Afrika'da Ekonomi Hukuku'nun Uyumlaştırılması Örgütü'nün muhasebe sistemi (SYSCOHADA) ile karşılaştırmaktır. Bu karşılaştırmalı analizin amacı, yukarıdaki iki muhasebe sisteminin benzerliklerini ve farklılıklarını ortaya koymaktır. Bu analiz UMS 1 : Finansal Tabloların Sunuluşu, UMS 2: Stoklar, UMS 7: Nakit Akış Tablosu, UMS 8: Muhasebe Politikaları, Muhasebe Tahminlerinde Değişiklikler Ve Hatalar, UMS 10: Raporlama Döneminden Sonraki Olaylar, UMS 12 :Gelir Vergileri, UMS 16 :Maddi Duran Varlıklar, UMS 19 :Çalışanlara Sağlanan Faydalar, UMS 20 :Devlet Teşviklerinin Muhasebeleştirilmesi Ve Devlet Yardımlarının Açıklaması, UMS 21 :Kur Değişiminin Etkileri, UMS 23 Borçlanma Maliyetleri, UMS 37 Karşılıklar, Koşullu Borçlar ve Koşullu Varlıklar, UMS 38 Maddi Olmayan Duran Varlıklar açısından yapılan muamelelere odaklanacaktır. Çalışma, her iki muhasebe standardı hakkında da iyi bir anlayışa sahip olmayı sağlayacaktır. Bu nedenle, yatırımcılar ve diğer tüm kişiler, SYSCOHADA ve Uluslararası Muhasebe Standartları ile ilgilenenler, bu iki muhasebe standardının finansal tablolarının karşılaştırılabilirliğini kolaylaştırmak amacıyla muhasebe düzenlemeleri hakkında iyi bir anlayışa sahip olabileceklerdir. Çalışma sonucunda SYSCOHADA ile Uluslararası Muhasebe Standartları arasındaki karşılaştırma birçok benzerlik ve çok az farklılık ortaya koymaktadır. Kıta Avrupası muhasebe sistemi ve Anglo-Sakson sisteminden kaynaklanan SYSOHADA hükümleri, kaynaklarını Uluslararası Muhasebe Standartlarında bulmaktadır. Ancak, bu iki standarttaki en büyük fark, SYSCOHADA için tarihsel maliyet ölçüm yöntemi ile UFRS için gerçeğe uygun değer arasındadır. In the face of the globalization of economies and the globalization of markets, the desire to have a common language is increasingly felt. To alleviate this need, many countries around the world have considered it appropriate to adopt IFRS standards for quality and comparable information. At this momentum, the OHADA field, through the SYSCOHADA accounting system, has decided to harmonize its standards with IFRS in 2017. The purpose of this study is to compare the International Accounting Standards (IAS/IFRS) with the accounting system of the Organization for the Harmonization of Economic Law in Africa (SYSCOHADA), which manages the accounting of all its assets in seventeen countries. The purpose of this comparative analysis is to reveal the similarities and differences of the above two accounting systems. This analysis will focus on the treatment of IAS 1 : presentation of financial statements IAS 2: Inventories IAS 7-cash flows IAS 8 accounting policies, changes in accounting estimates and errors IAS 10: events after the reporting period IAS 12 income taxes IAS 16 :property, plant and equipment assets IAS 19 :employee benefits IAS 20 :accounting for government grants and government assistance, description of TMS 21 :the effects of changes in foreign exchange rates IAS 23 borrowing costs, IAS 37 Provisions, Contingent Liabilities and Contingent Assets, IAS 38 intangible assets . The study will allow to have a good understanding on both accounting standards. Therefore, investors and all others persons interested in the SYSCOHADA and International Accounting Standards will be able to have a good understanding on the accounting regulations in order to facilitate the comparability of the financial statements of these two accounting standards. As a result of the study, the comparison between the SYSCOHADA and international accounting standards reveals many similarities and few differences. Originating from the continental European accounting system and the Anglo-Saxon system, the provisions of the SYSOHADA find their sources in International Accounting Standards. However, the major difference in these two standards is between the historical cost measurement method for the SYSCOHADA and the fair value for IFRS.
Keywords: Accounting; Accounting standards; African countries; Afrika Ticaret Kanunu Uyum Örgütü; Afrika ülkeleri; Comparative analysis; Comparison; International Accounting Standards; International accounting; Karşılaştırma; Karşılaştırmalı analiz; Muhasebe; Muhasebe standartları; Organization for the Harmonization of African Business Law; Uluslararası Muhasebe Standartları; Uluslararası muhasebe

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

Conflict Management over Maritime Territories : Use of ADR in Maritime Disputes: Kenya vs Somalia - Mwala, Natasha Lulia (Universität Wien, 2022)
The recent discoveries of natural resources on both territorial and maritime borders have heightened the probability of conflicts between states specifically in the Horn of Africa and the Greater Lakes Region. As a highly volatile region, conflicts are not a foreign phenomenon which have been plaguing the region since transition to the post-colonial era. It is simple to argue that the cause of disputes is due to the arbitrary borders drawn by the European powers, however, the region is experiencing a contemporary ‘scramble and petition’ with countries racing to exploit and gain over the newfound resources. In addition to this, the rise of nationalist sentiments combined with the burgeoning population and struggle of governments to finance their domestic budgets while trying to reduce borrowing from foreign markets due to the inflation costs which makes it expensive, also plays a key role in the quest to benefit from mineral exploration and excavation. While traditional conflicts rose from land border disputes that escalated to violence especially between border communities, maritime conflicts tend to be handled in legal ways with parties seeking intervention from bodies such as the International Tribunal of the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). Most cases are solved by outright delimitation of the maritime borders rather that joint management of marine land masses or natural resources based on mutual understanding or mutually assured benefits. The recent Kenya-Somalia Maritime dispute is an excellent case study. The aim of this research is to not only show alternative dispute resolution methods that can be used in maritime border disputes but also analyse the switch from pacific means of settlement of disputes to judicial intervention of the court. It begins by looking at the evolution of land border disputes between the two states, touches on the maritime dispute and their diplomatic, economic and security relationship. It further critically analyses the points of view of the two countries and the court’s ruling. Finally, it examines alternative dispute settlement mechanism that could have been used.
Keywords: ICJ; Joint maritime agreement; LOS; Maritime boundary dispute; Maritime délimitation; Memorandum of understanding

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

A posição do setor empresarial público no mercado angolano : seus reflexos no direito da concorrência em Angola - Pedro, João Manuel (Universidade de Lisboa, 2022)
O Regime Jurídico do Direito da Concorrência em Angola é recente. Com este regime pretende-se que o mercado angolano tenha como fundamento as regras que estabelecem as bases comuns de relacionamento entre os diferentes agentes económicos do mercado. A actual Lei Constitucional Angolana estabelece o princípio da coexistência de diversos tipos de sectores de actividades, nomeadamente, (i) o sector público, (ii) sector privado e (iii) cooperativo, garantindo a todos igualdade de oportunidades e liberdade económica, mas sujeitando-os aos princípios universais e modernos da economia de mercado, na base dos princípios e valores da sã concorrência, da moralidade e da ética. De acordo com a orientação constitucional, Angola possui um sistema de economia de mercado, todavia, o que se verifica na prática é a presença de um sector empresarial público forte e robusto, como resultado do sistema económico que vinha vigorando desde a independência, por um lado, e da existência de uma legislação conservadora que limita a liberdade de iniciativa do sector privado, mantendo boa parte das actividades económicas como áreas de reservas do Estado, por outro lado. Ao mesmo tempo que se verifica a resistência do Estado em manter áreas reservadas apenas para o sector público, assistimos a ascensão do Direito da Concorrência e os princípios a ele inerentes. Hoje, a legislação pertinente sobre o sector económico orienta-nos para uma visão que privilegie a concretização da economia de mercado e, por isso mesmo, muitos actos têm sido praticados com este fim, nomeadamente, mas sem a isto se limitar, foram actualizadas a Lei do Sector Empresarial Público, a Lei de Base das Privatizações e outras conexas, todas no sentido de adequa-las ao novo figurino da Constituição Angolana e ao novo regime do Direito da Concorrência. A questão é saber se todos estes actos e o próprio conteúdo da Lei da Concorrência permitem-nos afirmar, sem reservas, que o peso que o sector empresarial público tem no mercado angolano é controlado e não viola as regras elementares do Regime Jurídico do Direito da Concorrência.
Keywords: Angola; Autoridades de regulação; Competencia; Competition law; Direito da concorrência; Economia de mercado; Estado regulador; Market economy; Regulatory authorities; Sector empresarial do Estado; State business sector; State regulator

La simplification de la réglementation locale des aérodromes français - Peturaud, Charly (Aix-Marseille Université, 2022)

L'attractivité du pavillon britannique après le BREXIT - Ramelet, Norine (Aix-Marseille Université, 2022)

A legal comparison on the effectiveness of judicial management in Botswana against business rescue in South Africa - Topi, Sharon (University of Johannesburg, 2022)
Please refer to full text to view abstract.

La sécurité dans l'exploitation des porte-conteneurs - Vandame, Marie (Aix-Marseille Université, 2022)

Les ventes en sauvetage dans le milieu maritime - Viriot, Lucie (Aix-Marseille Université, 2022)

Os impactos da IFRS 16 e as suas determinantes – um estudo de caso, a TAP, Transportes Aéreos Portugueses - Xavier, Catarina Isabel (Universidade do Porto, 2022)